Notoginsenoside R1 attenuates tendinopathy through inhibiting inflammation and matrix metalloproteinases expression - Han, Qingxin; Wu, Junying; Li, Yan; Tong, Yi; Liu, Xiaohua; Hu, Xiaoqing; Zhang, Lei (Frontiers in Pharmacology, 2025)
Research purposeThe purpose of this study is to demonstrate the effectiveness of Notoginsenoside R1 (NGR1) in treating tendinopathy and to reveal its potential mechanisms.Materials and methodsThis study performed a preliminary network-based assessment of the potential targets that NGR1-associated in the treatment of tendinopathy, which includes PPI network analysis, GO enrichment, KEGG pathway enrichment analysis, and molecular docking. The therapeutic efficacy of NGR1 in vivo was then assessed using a collagenase-induced rat model of tendinopathy. Furthermore, the underlying mechanism was explored through LPS-induced inflammatory responses in tenocytes in vitro.ResultsNetwork-based assessment indicated that key targets associated with NGR1 in treating tendinopathy may potentially include IL-6, TNF, and MMP9. In vivo studies revealed that NGR1 mitigates the pathological response of tendinopathy induced by collagenase, exhibiting a dose-dependent efficacy, with the 8 μM concentration yielding the most favorable outcomes. RNA sequencing analyses of tenocytes indicated that NGR1 potentially treats tendinopathy by modulating the synthesis of collagen and matrix metalloproteinases, as well as attenuating LPS-induced inflammatory responses. These findings aligned with results obtained from quantitative PCR, ELISA and Western blot analyses.ConclusionNGR1 effectively moderates the progression of tendinopathy by modulating inflammatory reactions and matrix metabolism. This discovery offers a promising approach for clinical management of tendinopathy.